And yet it grows: Crisis, ideology, and interventionist policy ratchets - Christian Bjørnskov; Martin Rode (Research Institute of Industrial Economics (IFN), 2016)
Previous studies of policy responses to economic crises argue that crises may lead to more interventionist policy but also cause deregulation. The empirical evidence in previous studies is equally mixed. The present paper argues that whether or not governments implement more or less interventions depend on their core political ideology. We thus expect ideologically heterogeneous policy reactions to crises yet also note that crisis responses theoretically may cause "policy ratchets" where temporary crisis policies become permanent. Employing a panel of 68 countries with Western political institutions observed between 1975 and 2010, and exploring the evolution of indicators of government size and regulatory policy, we find that crises in general cause more interventionist policies when countries have centrist or left-wing governments. We also find clear evidence of policy ratchets in all policy areas. The ideological crisis policies mainly relate to government consumption and market regulations
Keywords: D72; H70; H11; 330; Economic crisis; Regulation; Government consumption; Government ideology